DIMENSI RASULI PERJALANAN PERTOBATAN ST. IGNATIUS LOYOLA (Apostolic dimension of St. Ignatius’ conversion journey) - Sardi, Leo Agung (Sanata Dharma University, 2023)
It is not since at the beginning of his spiritual journey we see the apostolic dimension of the life of St. Ignatius that there after characterizes the Ignatian spirituality. The apostolic dimension is part of his process of conversion journey. By studying on his conversion specially his experiences in Manresa, I show the apostolic dimension of St. Ignatius’ conversion. This presented paper indicates the moment in which there are some indications of the apostolic dimension of his conversion. Furthermore, this paper presents that at the long way of his spiritual journey, the apostolic dimension was growing stronger and characterizes the Ignatian spirituality until now. Part of his way of conversion and his spiritual life, the motif that moved St. Ignatius decided to study and to look for friend in Paris was his apostolic spiritual vision synthetized in ayudar a las almas (to help souls).